KONSEP PERANCANGAN DAN PENGEMBANGAN SARANA DAN MEDIA PEMBELAJARAN DI KABUPATEN SIDOARJO - Mohamad Febry Ardiansyah; Failasuf Herman Hendra; Siti Azizah (Prosiding Seminar Nasional Sains dan Teknologi Terapan, 2022)
Sidoarjo Regency as one of the buffers for the capital city of East Java Province is an area that is experiencing rapid development in the education sector. Tutoring program to develop study habits that develop in the era of globalization where the challenges and competition to obtain the best formal education is getting tougher and competitive. Facilities in the form of learning facilities and media are needed to improve the quality of education in Sidoarjo Regency.The design and development of learning facilities and media carries the theme of Green Architecture which is then revealed to the macro concept of "Recreation" as a place for developing student learning activities as well as facilities for enriching learning facilities and media. The micro concept of "Cluster" land arrangement is intended so that visitors can enjoy a series of pleasant environmental views. The micro concept of “Attractive” form is to create a unique building display where the contrasting, dynamic, and surprising characters in the composition of the mass, facade, circulation between masses are in such a way. The micro concept of "Natural" space is used to form a beautiful room atmosphere by emphasizing the elements of vegetation and a comfortable space atmosphere.Green architecture that allows the learning process to be more comfortable and a healthy environment is expected to improve the quality of learning effectively, efficiently and fun. Therefore, the design and development of learning facilities and media in Sidoarjo, Gedangan District, Sidoarjo Regency is very necessary.